2007
DOI: 10.1103/physrevlett.98.026105
|View full text |Cite
|
Sign up to set email alerts
|

Hexagon versus Trimer Formation in In Nanowires on Si(111): Energetics and Quantum Conductance

Abstract: The structural and electronic properties of the quasi-one-dimensional In=Si111 surface system are calculated from first principles. It is found that the symmetry lowering of the In chains is energetically favorable, provided neighboring nanowires are correlated, giving rise to a doubling of the surface unit cell both along and perpendicular to the chain direction. The recently suggested formation of hexagons within the In nanowires [C. González, F. Flores, and J. Ortega, Phys. Rev. Lett. 96, 136101 (2006)]-in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 35 publications
3
70
2
Order By: Relevance
“…The 4 ϫ 1 unit cell is indicated. Adapted from Stekolnikov et al, 2007. structure is nicely captured by the various DFT calculations ͑Cho et , 2005Wang et al, 2003;González et al, 2005González et al, , 2006bTsay, 2005;López-Lozano et al, 2006;Cho and Lee, 2007;Stekolnikov et al, 2007͒ for the structure model by Bunk et al ͑1999͒. Figure 18 shows the experimentally determined Fermi contours of all three bands ͑Ahn, Byun, et al, 2004͒.…”
Section: Atomic and Electronic Structurementioning
confidence: 99%
See 3 more Smart Citations
“…The 4 ϫ 1 unit cell is indicated. Adapted from Stekolnikov et al, 2007. structure is nicely captured by the various DFT calculations ͑Cho et , 2005Wang et al, 2003;González et al, 2005González et al, , 2006bTsay, 2005;López-Lozano et al, 2006;Cho and Lee, 2007;Stekolnikov et al, 2007͒ for the structure model by Bunk et al ͑1999͒. Figure 18 shows the experimentally determined Fermi contours of all three bands ͑Ahn, Byun, et al, 2004͒.…”
Section: Atomic and Electronic Structurementioning
confidence: 99%
“…Stekolnikov et al ͑2007͒ also found the 4 ϫ 2 hexagon structure to be metastable but obtained a stable 8 ϫ 2 arrangement. 9 The strongest evidence in favor of the hexagon model is the observation of a nonmetallic ground state.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indium atoms on Si(111) form NWs with a metallic character, [30][31][32][33][34][35][36][37] but also on high-index surfaces, such as Si(557), atomic wires are observed. 38 This is similar to Au, which preferentially forms chains on the high-index surfaces like Si(553) 17,20,[39][40][41] and Si(557) 20,25,40,[42][43][44][45][46] .…”
Section: Introductionmentioning
confidence: 99%